Prompting by COVID-19 to Rethink the Purpose of Engineering Laboratory Education -- Develop Practical Competence to Solve Real-World Problems - Leung, Siu Ling; Hargrove, Brianne A; Marsh, Eric R; Gregg, Andrea R; Thole, Karen A (Advances in engineering education, 2020)
Today's engineering laboratory education often lacks opportunities for students to practice critical thinking through real-world problems. This particular objective is even harder to achieve through online laboratory experiments. In this article, we summarize our innovation in using a real-world challenge, analyze big data, to empower student data analysis skills in remote teaching platform. This approach allows students to collect data, analyze, and evaluate possible solutions continuously through hands-on experimentation with accessible resources around them. Compared to the video-recorded lab, our method achieves a higher level of learning in Bloom's taxonomy. To further improve our approach, we summarize our lesson learned from transferring six different engineering laboratory courses online, in response to the COVID-19. A thriving 21st-century learning environment has to embrace agility, create flexibility, adapt to technology, and support virtual team collaborations.